Activation of basal forebrain purinergic P2 receptors promotes wakefulness in mice - Chun Yang (Nature Portfolio, 2018)
Abstract The functions of purinergic P2 receptors (P2Rs) for extracellular adenosine triphosphate (ATP) are poorly understood. Here, for the first time, we show that activation of P2Rs in an important arousal region, the basal forebrain (BF), promotes wakefulness, whereas inhibition of P2Rs promotes sleep. Infusion of a non-hydrolysable P2R agonist, ATP-γ-S, into mouse BF increased wakefulness following sleep deprivation. ATP-γ-S depolarized BF cholinergic and cortically-projecting GABAergic neurons in vitro, an effect blocked by antagonists of ionotropic P2Rs (P2XRs) or glutamate receptors. In vivo, ATP-γ-S infusion increased BF glutamate release. Thus, activation of BF P2XRs promotes glutamate release and excitation of wake-active neurons. Conversely, pharmacological antagonism of BF P2XRs decreased spontaneous wakefulness during the dark (active) period. Together with previous findings, our results suggest sleep-wake regulation by BF extracellular ATP involves a balance between excitatory, wakefulness-promoting effects mediated by direct activation of P2XRs and inhibitory, sleep-promoting effects mediated by degradation to adenosine.